Features of Ukrainian enterprises in the environmental protection field and the formation of an effective environmental strategy - Bakina, Tetiana; Бакіна, Тетяна Володимирівна; Бакина, Татьяна Владимировна (My University, 2019)
Issues of environmental management, environmental protection and environmental safety have now become the most important political issues that are being addressed at the international level. Traditionally, various methods of pollutant disposal were used to solve environmental problems, which were formed in the process of production, the focus was on technical and technological aspects. At the present stage of scientific and technological progress, along with increasing environmental requirements for production technologies, which provide transition from elimination of consequences to management of pollution at all stages of the made production life cycle, management comes to the fore and becomes a decisive factor in the economy, determining the further effective development. Thus, in solving environmental problems of the enterprise in modern conditions, more attention is paid to management, politics, culture, which finds their expression in the style and methods of management
Keywords: protection of the environment; environmental strategy; management; solving environmental problems